Expansion of plasmablasts and loss of memory B cells in peripheral blood from COVID‐19 patients with pneumonia. Issue 9 (13th August 2020) - De Biasi, Sara; Lo Tartaro, Domenico; Meschiari, Marianna; Gibellini, Lara; Bellinazzi, Caterina; Borella, Rebecca; Fidanza, Lucia; Mattioli, Marco; Paolini, Annamaria; Gozzi, Licia; Jaacoub, Dina; Faltoni, Matteo; et al.
Abstract: Studies on the interactions between SARS‐CoV‐2 and humoral immunity are fundamental to elaborate effective therapies including vaccines. We used polychromatic flow cytometry, coupled with unsupervised data analysis and principal component analysis (PCA), to interrogate B cells in untreated patients with COVID‐19 pneumonia. COVID‐19 patients displayed normal plasma levels of the main immunoglobulin classes, of antibodies against common antigens or against antigens present in common vaccines. However, we found a decreased number of total and naïve B cells, along with decreased percentages and numbers of memory switched and unswitched B cells. On the contrary, IgM + and IgM − plasmablasts were significantly increased. In vitro cell activation revealed that B lymphocytes showed a normal proliferation index and number of dividing cells per cycle. PCA indicated that B‐cell number, naive and memory B cells but not plasmablasts clustered with patients who were discharged, while plasma IgM level, C‐reactive protein, D‐dimer, and SOFA score with those who died. In patients with pneumonia, the derangement of the B‐cell compartment could be one of the causes of the immunological failure to control SARS‐Cov2, have a relevant influence on several pathways, organs and systems, and must be considered to develop vaccine strategies. Abstract : Through Principal Component Analysis combining clinical data with those regarding B cells, we identify important factors that tip the balance toward patient discharge or death. The window of opportunity represents the moment in which therapies that blocks IL‐6 pathway and acts on different cell types can be used.